Optimum design and performance of a solar dish microturbine using tailored component characteristics. (1st December 2018) - Gavagnin, Giacomo; Rech, Sergio; Sánchez, David; Lazzaretto, Andrea
Highlights: System cycle and geometries tailored to each set of boundary conditions are obtained. Solar-to-electric efficiency of 18–22% are achievable for a pressure ratio of 3.2. Different optimum design values of DNI are found considering different locations. System efficiency drops as much as 50% if a non-optimal design DNI is selected. The efficiency drop is stronger in locations with low DNI (<700 W/m 2 ). Abstract: The aim of the paper is to find the optimum design and performance of solar microturbines powered by parabolic dish collectors using an innovative methodology which integrates the design and off-design models of the total system. In contrast to the common practice of assigning an estimated efficiency to the engine turbomachinery (generalized performance maps), the procedure hereinafter produces the specific geometry and the characteristic maps of compressor and turbine, according to their inlet/outlet thermodynamic states and working cycle boundary conditions. With this global approach, a sensitivity analysis is performed to search for the pressure ratio that maximizes the solar-to-electric efficiency at design point for a constant air mass flow rate and turbine inlet temperature. Maximum values in the range 18.0–21.7% are obtained for a pressure ratio of 3.2 when the turbine inlet temperature changes between 800 °C ( base-case system) and 900 °C. The methodology allows also to simulate the performance of the system when different design DNIs are considered with the aim to maximize the annual yield of the system. Simulations performed for Beijing, Seville and San Diego showed that quite different DNIs (610–815 W/m 2 ) are to be chosen to get the maximum annual (average) efficiency: 11–16% for the base-case system and 14–19% for a more advanced design.